Reconciling livestock production and wild herbivore conservation: challenges and opportunities - Pozo, R. A.; Cusack, J. J.; Acebes, P.; Malo, J. E.; Traba, J.; Iranzo, E. C.; Morris-Trainor, Z.; Minderman, J.; Bunnefeld, N.; Radic Schilling, Sergio Javier; Moraga, C. A.; Arriagada, R.; et al. (My University, 2021)
Increasing food security and preventing further loss of biodiversity are two of humanity's most pressing challenges. Yet, efforts to address these challenges often lead to situations of conflict between the interests of agricultural production and those of biodiversity conservation. Here, we focus on conflicts between livestock production and the conservation of wild herbivores, which have received little attention in the scientific literature. We identify four key socio-ecological challenges underlying such conflicts, which we illustrate using a range of case studies. We argue that addressing these challenges will require the implementation of co-management approaches that promote the participation of relevant stakeholders in processes of ecological monitoring, impact assessment, decision-making, and active knowledge sharing.
Keywords: co-management; coexistence; conflict; food security; livestock husbandry